2016
DOI: 10.1016/j.chb.2016.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interface and spatial ability on manipulation of virtual models in a STEM domain

Abstract: Virtual models are increasingly employed in STEM education to foster learning about spatial phenomena. However, the roles of the computer interface and students' cognitive abilities in moderating learning and performance with virtual models are not yet well understood. In two experiments students solved spatial organic chemistry problems using a virtual model system.Two aspects of the virtual model interface were manipulated: display dimensionality (stereoscopic vs. monoscopic displays) and the location of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 52 publications
1
22
0
3
Order By: Relevance
“…from which others originating from technology and engineering are incorporated, as well as developing skills from the three disciplines studied. Likewise, Barrett and Hegarty (2016) study molecular structure in their educational intervention, incorporating technological tools (software for creating two-dimensional [2D] and 3D models), and engineering knowledge and skills to complement the teaching of the scientific content described.…”
Section: Research Questions 2 and 3 Stem Disciplinesmentioning
confidence: 99%
“…from which others originating from technology and engineering are incorporated, as well as developing skills from the three disciplines studied. Likewise, Barrett and Hegarty (2016) study molecular structure in their educational intervention, incorporating technological tools (software for creating two-dimensional [2D] and 3D models), and engineering knowledge and skills to complement the teaching of the scientific content described.…”
Section: Research Questions 2 and 3 Stem Disciplinesmentioning
confidence: 99%
“…Evidence in favor of this hypothesis comes from a meta-analysis of 27 experiments, in which Höffler (2010) showed low spatial ability learners benefitted more from animations versus static pictures, or 3D versus 2D illustrations compared to high spatial ability learners. However, more recent studies showed mixed results, with some reporting benefits of additional spatial information for low spatial ability (Barrett & Hegarty, 2016;Kühl, Stebner, Navratil, Fehringer, & Münzer, 2018;Lee & Wong, 2014;Münzer, 2015;Sanchez & Wiley, 2014), and others reporting benefits for high spatial ability groups (Vindenes, de Gortari, & Wasson, 2018;Wu, Lin, & Hsu, 2013). When virtual learning environments were used in these studies, these were predominantly of the non-immersive kind, with a few notable exceptions (e.g.…”
Section: Spatial Abilitymentioning
confidence: 99%
“…When virtual learning environments were used in these studies, these were predominantly of the non-immersive kind, with a few notable exceptions (e.g. Barrett & Hegarty, 2016;Vindenes et al, 2018). For research focusing on the learning benefits of CAVEs, individual differences due to spatial visualizations are expected to be critical because of users spatially moving around in the virtual world.…”
Section: Spatial Abilitymentioning
confidence: 99%
“…According to Sarıtas (2015) meaningful construction of knowledge on molecular geometry by pre-service chemistry teachers has always been a great challenge of chemistry learning leading to misconceptions. However, recently, virtual reality technology (VRT) has been widely proposed to serve as an innovative technology for providing highly immersive and interactive chemistry class with three-dimensional learning environment (Al-Balushi, Al-Musawi, Ambusaidi, & Al-Hajri, 2017; Barrett & Hegarty, 2016) . Therefore, chemistry teacher candidates possessed positive beliefs about VR technology in enhancing understanding, motivation, and schematic thinking schematically.…”
Section: R E S U L T Smentioning
confidence: 99%